Strategy for Expanding Nutrition Professionals' Competency: A Pilot Case Study in Dissemination and Implementation Science Training - Ayron E. Walker; Elizabeth A. Claydon; Samantha Scarneo-Miller; Daniel Totzkay; Melissa D. Olfert (New Prairie Press, 2023)
Dissemination and Implementation (D&I) science trainings are essential to build knowledge for a variety of current and future health professionals. The objective of this study was to pilot-test and assess implementation of a nutrition-specific D&I science training. Participants (students enrolled in nutrition and public health programs) completed pre/post surveys and exit interviews. We used descriptive statistics and qualitative thematic analysis with deductive coding, in which coding and theme development were directed by existing concepts. Initial coding was completed by one researcher and validated by an additional researcher to describe and provide examples of the categories of the Kirkpatrick Model and Implementation Outcomes Framework. The evaluation of training was positively supported through the Kirkpatrick Scale results (mean scores between 6.94 ± 1.7 (Learning) and 7.35 ± 1.9 (Reaction)) and qualitative findings (increased confidence in D&I science and positive feedback on active learning strategies (application-based learning, mentorship, and discussions). Participants (n = 8) described the learning activities (case studies, discussions, projects), the structure of the course (flipped classroom, content, learning strategies), the setting (hybrid, online), and mentorship (continuous feedback on assignments) as enabling effective implementation, which reflect with positive Implementation Outcome findings (3.59 ± 1.26, appropriateness score 3.94 ± 0.85, and feasibility score of 4.09 ± 0.67). These findings support positive implementation feasibility and program evaluation. Future studies need to compare changes in knowledge, attitudes, and beliefs among current or future nutrition professionals before and after completing this training.